School Strategy for Preparing Kindegarten Transitional Children to Elementary School - Maharani, Hanum Alfitrah; Nabila, Sya’bania Laila; Nisa, Gitsa Zahrotun; Amarta, Roisah Adiliah (Universitas Muhammadiyah Sidoarjo, 2024)
The transition from early childhood education to primary school is a crucial period in a child's educational development. The learning environment provided during this phase plays an important role in supporting adaptation, social-emotional development and academic skills. The aim of the study was to explore the role of the environment in the ECD to primary school transition. This study describes the perspectives and practices of mothers about elementary school readiness in the area of Darussalam kindergarten temple the purpose of the observation is to do the field introduction article of the school and to get information about various concepts and habits of school discipline and transition and get insight from various regulations related to the priority of preparation for elementary school, we as researchers collect with qualitative data first by observation and conducting questions and answers during the week The results of the observation show that the disciplinary policy affects school readiness and transition in the field the results of this study also provide little input on the concept of school readiness by paying attention to educators' beliefs about child development (school readiness and transition).